Preparation and characterization of calcium carboxymethyl cellulose/chitosan blend nonwovens for hemostatic agents. Issue 16 (August 2018) - Kim, Ga Hee; Im, Jung Nam; Kim, Tae Hee; Lee, Gyu Dong; Youk, Ji Ho; Doh, Song Jun
Wet-laid blend nonwovens of calcium carboxymethyl cellulose fibers and chitosan powder were prepared as a new efficacious hemostatic agent, and their water absorption behavior, rupture strength in the dry and wet states, blood clotting properties, calcium ion release behavior, and cytotoxicity were investigated. The calcium carboxymethyl cellulose and chitosan nonwovens lost their structural integrity in the wet state due to water absorption and subsequent gelation, whereas the calcium carboxymethyl cellulose/chitosan blend nonwovens maintained their structural integrity. The formation of polyelectrolyte complexes between calcium carboxymethyl cellulose and chitosan after the absorption of water is believed to have contributed to the structural integrity in the wet state. In the in vitro blood clotting tests, the calcium carboxymethyl cellulose/chitosan blend nonwovens immediately absorbed blood and exhibited efficacious blood clotting characteristics. The calcium carboxymethyl cellulose/chitosan blend nonwovens were not cytotoxic. Considering both the structural stability in the wet state and blood clotting performance, calcium carboxymethyl cellulose/chitosan (7/3 w/w) blend nonwoven was found to be the most effective hemostatic agent of those assessed in this study, and has good potential for commercial application.